Research on Machining Fixture of Near-Net-Shaped Jet Engine Blade. (October 2019) - Wu, Dongbo; Chen, Yunhai; Zhen, Xuesong; Zhang, Kaiyao
Abstract: This paper focus on the design and verification of the machining fixture on the background of the adaptive processing technology. Firstly, the positioning and clamping scheme of near-net-shaped jet engine blades are introduced and analyzed, especially the new materials (Polyetheretherketone (PEEK-GF30)) and new structure are applied to fixture, and corresponding fixture is designed, manufactured and applied to engineering. Secondly, the relationship between the blade clamping deformation and clamping force is analyzed by finite element method (FEA). Thirdly, blade cutting deformation is analyzed by cutting experiment. The results show that this new material and structure fixture combined with CNC adaptive processing technology can achieve the precision machining of near-net-shaped jet engine blades Tenon root.